2013
DOI: 10.1038/laban.161
|View full text |Cite
|
Sign up to set email alerts
|

A co-housing strategy to improve fecundity of mice in timed matings

Abstract: Timed matings of mice are often carried out to obtain offspring of a precise age when required for a study. Timed matings involve housing male and female mice together for a limited time period, typically overnight. A limitation of this practice is that many mouse pairs fail to mate during the brief co-housing period. The authors co-housed each breeding pair in the same cage but separated by a transparent partition for 3 d before carrying out timed matings. This co-housing strategy resulted in increased copula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Results are given as the mean AE standard error of the mean (SEM). effect with co-housing as suggested by Stiles et al 7 Surprisingly, even without using such approaches, we observed more plug-positive females after overnight mating than expected. Whitten 8 showed that only 13-14% of young virgin females had a vaginal plug on the first two days after mating.…”
Section: Discussionsupporting
confidence: 71%
“…Results are given as the mean AE standard error of the mean (SEM). effect with co-housing as suggested by Stiles et al 7 Surprisingly, even without using such approaches, we observed more plug-positive females after overnight mating than expected. Whitten 8 showed that only 13-14% of young virgin females had a vaginal plug on the first two days after mating.…”
Section: Discussionsupporting
confidence: 71%
“…To the Group IV animals, 10 ppm of Hg Chloride was administered and Group V and VI were administrated 10 ppm of HgCl 2 along with 150 and 300 ppm of Curcumin. On the day of pregnancy the animals were divided into three subgroups and the experiments were carried out as described by Stiles et al (2013).…”
Section: Methodsmentioning
confidence: 99%
“…To improve the success of timed matings when female and male mice are housed together for a limited time, breeding pairs can be maintained in the same box separated by a transparent partition for 3 days before setting up the timed mating. This permits male urine-borne pheromones to induce female estrus, thereby enabling the expression of male and female mating behaviors ( Stiles et al, 2013 ).…”
Section: Effects Of Environment On Ethologically Appropriate Behaviormentioning
confidence: 99%